2013
DOI: 10.5578/kvj.5251
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone: the Bioactive Component of Nigella Sativa

Abstract: ÖZET Nigella Sativa (NS),'dan izole edilen timokinon (TQ) özellikle antioksidan, antihiperlipidemik, antidiyabetik, antiinflamatuar, gastroprotektif, hepatoprotektif gibi pek çok yararlı etkilere sahiptir. Bu derlemede TQ'nun biyokimyasal ve fizyolojik özellikleri özetlenmiştir. ••• Thymoquinone: The Bioactive Component of Nigella Sativa S U M M A R Y Thymoquinone (TQ) which was isolated from Nigella Sativa (NS), particularly has the beneficial effects such as antioxidant, anticancerogenic, antihyperlipidemic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…TQ also has inhibitory effects on the proliferation of many types of cancer cells (Bacak Güllü & Avcı, 2013). In the literature review, some studies have been found on the quality of semen after freezing and thawing with semen extenders supplemented with TQ or N. sativa oil on ram, buck and buffalo semen (Awan et al, 2018;Miah et al, 2018;Shikh Maidin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TQ also has inhibitory effects on the proliferation of many types of cancer cells (Bacak Güllü & Avcı, 2013). In the literature review, some studies have been found on the quality of semen after freezing and thawing with semen extenders supplemented with TQ or N. sativa oil on ram, buck and buffalo semen (Awan et al, 2018;Miah et al, 2018;Shikh Maidin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…TQ is known to have anti‐inflammatory, antioxidant, neuroprotection (Radad et al, 2009) properties, as well as a recovery effect against oxidative stress induced in neuropathy (Hamdy & Taha, 2009). TQ also has inhibitory effects on the proliferation of many types of cancer cells (Bacak Güllü & Avcı, 2013). In the literature review, some studies have been found on the quality of semen after freezing and thawing with semen extenders supplemented with TQ or N. sativa oil on ram, buck and buffalo semen (Awan et al, 2018; Miah et al, 2018; Shikh Maidin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although black cumin shows many differences in agricultural and quality characteristics according to the regions where it is cultivated, generally in the structure of the seed, it contains 0.4-0.45% essential oil, 32-40% fatty oil, 16-19.9% protein, 33.9% carbohydrates, 5.5% saponins, alkaloids and fibers, 1.79%-3.44% tannins and minerals. While there are unsaturated fatty acids such as linoleic acid, oleic acid and linolenic acid in its fatty oil, it contains palmitic acid, stearic acid and myristic acid from saturated fatty acids (Güllü and Avcı, 2013). Black cumin essential oil contains bioactive substances such as thymoquinone, p-cymene, nigellonethyllinoleate, α-thujen, thymol, α-pinene, carvacrol, trans-anethol, β-pinene.…”
Section: Introductionmentioning
confidence: 99%
“…TQ is the most important bioactive ingredient found in black cumin oil (Nigella sativa). Black cumin and TQ were reported to have anticancerogenic, antiulcerogenic, antiinfl ammatory and antioxidant effects (6). Their favourable effects on cardiac injury induced by certain medications (7) (8) and ischemia-reperfusion (9) have been previously reported; however, very few studies have reported the protective effects of TQ on the heart against DXR-induced toxicity (10,11).…”
Section: Introductionmentioning
confidence: 99%